Influence of Outplacement on the Protection of Workers Competencies - Andrzej Klimczuk; Magdalena Klimczuk-Kochańska (Aktuálne problémy podnikovej sféry 2013, 2013)
This paper presents the problem of workers lay off and loss along with their exit from the organization its key competencies - skills and knowledge. Importance of management of key competencies was described. The paper also presents outplacement as a way to maintain core competencies even during reducing the human resources within the enterprises.
Keywords: J21; J63; M14; O15; 330; competencies; downsizing; employment structure; human resources; Human resource planning; Labour Market